Nonstenotic carotid plaque on CT angiography in patients with cryptogenic stroke. (16th August 2016) - Coutinho, Jonathan M.; Derkatch, Sheldon; Potvin, Alphonse R.J.; Tomlinson, George; Kiehl, Tim-Rasmus; Silver, Frank L.; Mandell, Daniel M.
Abstract : Objective: To determine whether large (≥3 mm thick) but nonstenotic (<50%) carotid artery atherosclerotic plaque predominantly occurs ipsilateral rather than contralateral to cryptogenic stroke. Methods: This was a cross-sectional observational study. Using a stroke registry, we identified consecutive patients with anterior circulation embolic stroke of undetermined source (ESUS). Using CT angiography, we measured carotid plaque size (thickness, mm) and carotid artery stenosis (North American Symptomatic Carotid Endarterectomy Trial method) for each patient. We dichotomized plaque size at several predefined thresholds and calculated the frequency of plaque size above each threshold ipsilateral vs contralateral to stroke. Results: We included 85 patients with ESUS. Plaque with thickness ≥5 mm was present ipsilateral to stroke in 11% of patients, and contralateral in 1% (9/85 vs 1/85; p = 0.008). Plaque with thickness ≥4 mm was present ipsilateral to stroke in 19% of patients, and contralateral in 5% (16/85 vs 4/85; p = 0.002). Plaque with thickness ≥3 mm was present ipsilateral to stroke in 35% of patients, and contralateral in 15% (30/85 vs 13/85; p = 0.001). There was no difference in percentage stenosis ipsilateral vs contralateral to stroke ( p = 0.98), and weak correlation between plaque size and stenosis ( R 2 = 0.26, p < 0.001). Conclusions: Large but nonstenotic carotid artery plaque is considerably more common ipsilateral than contralateral to cryptogenic stroke, suggesting that nonstenotic plaque is an underrecognized cause of stroke. We measured plaque size using CT angiography, a method that could be easily implemented in clinical practice.